Pengembangan Dashboard Aplikasi Kasir dan Manajemen Meja Berbasis Web pada Usaha Kafe - Ardeco Sakha Agriel; Farizi Ilham; Joshua Ravael Hartono (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
The culinary industry, particularly café businesses, faces challenges in improving operational efficiency amid growing daily transaction volumes. Booster Coffee JKT, a café located in West Jakarta, still relies on a semi-manual system for transaction recording and table data management, leading to recording errors, lack of real-time data availability, and delays in sales report generation. This study aims to design and develop an integrated web-based cashier application and table management dashboard to improve operational efficiency and service quality. The methods employed include direct observation, interviews, literature review, and object-oriented system design visualized through UML diagrams and ERD. The system architecture is built on the Laravel framework using the Model-View-Controller (MVC) pattern with a relational database. The design results in a system capable of automating sales transaction recording, monitoring table status in real time, integrating ingredient inventory management, and presenting accurate operational reports through a unified interface. The system also supports Kitchen Display System (KDS) features, promotion and discount management, and role-based access control. The implementation of this system is expected to minimize recording errors, increase service speed, and support data-driven managerial decision-making.